Digital Citizenship During a Global Pandemic: Moving Beyond Digital Literacy. Issue 1 (17th July 2020) - Buchholz, Beth A.; DeHart, Jason; Moorman, Gary
Abstract: In this commentary, the authors move beyond digital literacy and take up the question of what digital citizenship means and looks like in the context of the COVID‐19 pandemic. To engage with questions of ethical practice, the authors begin with the International Society for Technology in Education framework for digital citizenship. They expand on these standards to argue for an awareness of the ethical questions facing citizens online that are difficult to encompass as a set of skills or competencies. The authors then take these considerations into a set of practical steps for teachers to nurture participatory and social justice–oriented digital citizenship as part of the curriculum. The authors conclude by noting the digital divide and social inequities that have been highlighted by the current crisis.